A hierarchal planning framework for AUV mission management in a spatiotemporal varying ocean. (April 2018) - MahmoudZadeh, Somaiyeh; M.W Powers, David; Sammut, Karl; Atyabi, Adham; Yazdani, Amirmehdi
Abstract: This paper provides a hierarchical dynamic mission planning framework for an AUV to accomplish task-assign process in a restricted time operating in uncertain undersea environment. A high-level reactive mission planner is developed for task priority assignment, guiding the vehicle toward a target of interest, and managing on-time mission completion. A low-level motion planner is also developed to handle unexpected changes of the dynamic terrain by re-generating optimal trajectories. The mission planner reactively re-arranges the tasks based on mission/terrain updates. As a result, the vehicle is able to undertake the maximum number of tasks with certain degree of maneuverability having situational awareness of the operating field. The Biogeography-Based Optimization (BBO) algorithm is used as the computational engine of the framework in both mission and motion planners. The simulations results indicate the significant potential of the proposed hierarchical framework in providing efficient solutions for mission success and its applicability for real-time implementation.